Tinderbox : how the West sparked the AIDS epidemic and how the world can finally overcome it - Timberg, Craig (Penguin Press, 2012)
"Washington Post reporter Craig Timberg and Harvard AIDS researcher Daniel Halperin, PhD, recount for the first time how Western colonial powers unwittingly sparked the AIDS epidemic and then fanned its rise. Drawing on remarkable new genetic discoveries, Tinderbox overturns the conventional wisdom on the origins of this deadly pandemic and the best means to fight it today"--